A prospective study of urinary pneumococcal antigen detection in healthy Karen mothers with high rates of pneumococcal nasopharyngeal carriage. - Turner, P; Turner, C; Kaewcharernnet, N; Mon, N; Goldblatt, D; Nosten, F (BioMed Central, 2011)
BACKGROUND: Detection of Streptococcus pneumoniae C-polysaccharide in urine is a useful rapid diagnostic test for pneumococcal infections in adults. In young children, high rates of false positive results have been documented due to detection of concurrent nasopharyngeal pneumococcal carriage. The relationship between pneumococcal carriage and urinary antigen detection in adults from developing countries with high pneumococcal carriage prevalence has not been well established. METHODS: We nested an evaluation of the BinaxNOW S. pneumoniae test within a longitudinal mother-infant pneumococcal carriage study in Karen refugees on the Thailand-Myanmar border. Paired urine and nasopharyngeal swab specimens were collected from 98 asymptomatic women at a routine study follow-up visit. The urine specimens were analyzed with the BinaxNOW test and the nasopharyngeal swabs were semi-quantitatively cultured to identify pneumococcal colonization. RESULTS: 24/98 (25%) women were colonized by S. pneumoniae but only three (3%) had a positive BinaxNOW urine test. The sensitivity of the BinaxNOW test for detection of pneumococcal colonization was 4.2% (95% CI: 0.1-21.1%) with a specificity of 97.3% (95% CI: 90.6-99.7%). Pneumococcal colonization was not associated with having a positive BinaxNOW test (odds ratio 1.6; 95% CI: 0.0-12.7; p=0.7). CONCLUSIONS: Significant numbers of false positive results are unlikely to be encountered when using the BinaxNOW test to diagnose pneumococcal infection in adults from countries with moderate to high rates of pneumococcal colonization.